2014
DOI: 10.7314/apjcp.2014.15.7.3247
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin S128R Polymorphism is Associated with Cancer Risk: a Meta-analysis

Abstract: Background: Genetic factors have been shown to play an important role in the development of cancers. However, individual studies may fail to completely demonstrate complicated genetic relationships because of small sample size. Therefore, we performed a meta-analysis to evaluate the association of E-selectin Ser128Arg (S128R) with cancer risk. Materials and Methods: A literature search in PubMed, Embase, Web of Science, Science Direct, SpringerLink, EBSCO, Wanfang, and Chinese National Knowledge Infrastructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Likewise, this allele was also linked to an elevated risk of relapse, metastasis and mortality among CRC patients [154][155][156]. A meta-analysis suggested rs5361 as an overall cancer risk factor among Caucasian and Asian ethnic groups [164]. In the same fashion as rs5361, rs5362 (A>G), rs5367 (A>G), and rs5368 (G>A) variant alleles were demonstrated to be associated with an increased risk of BC.…”
Section: E-selectinmentioning
confidence: 94%
“…Likewise, this allele was also linked to an elevated risk of relapse, metastasis and mortality among CRC patients [154][155][156]. A meta-analysis suggested rs5361 as an overall cancer risk factor among Caucasian and Asian ethnic groups [164]. In the same fashion as rs5361, rs5362 (A>G), rs5367 (A>G), and rs5368 (G>A) variant alleles were demonstrated to be associated with an increased risk of BC.…”
Section: E-selectinmentioning
confidence: 94%
“…This suggests that it is a functional polymorphism. Furthermore, previous research has shown that SELE polymorphisms play a role in susceptibility to carcinoma development to some extent [6]. Endothelial cells express SELE, a key adhesion molecule known for its involvement in facilitating cell-cell contacts between cancer cells and endothelial monolayers during metastasis [7].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that it is a functional polymorphism. Furthermore, previous research has shown that SELE polymorphisms play a role in susceptibility to carcinoma development to some extent [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The E-selectin S128R (A/C) polymorphism alters the binding specificity of the extracellular domain and thus facilitates ligand binding, which in turn improves the adhesion of lymphoid and myeloid cells to the endothelium [ 20 , 21 , 22 ]. In the E-selectin gene variants, the S128R polymorphism is of particular interest as it is clinically associated with increased cancer risk [ 23 ].…”
Section: Introductionmentioning
confidence: 99%